Ensino de conceitos geométricos por meio do desenho geométrico - Armando, Barbara Ribeiro Silva (2023)
The present work aimed to evaluate the reflections and potentialities of the Geometric Design subject as an elective in the list of possibilities linked to the reformulation of the “New Secondary School 2022”. We intend to build arguments and examples that prove the potential of this discipline as a didactic-pedagogical support to the teaching of Mathematics and, in particular, to the teaching of Geometry. We initially highlight historical aspects of Geometric Design; elements that map the development of the geometric thinking of the students involved according to Van Hiele’s theory and the use of computer programs, alternative to constructions with ruler and compass, usually present in the environment of Geometric Design. We built, applied and analyzed evaluative processes, regarding the cognitive levels of freshmen, highlighting the absence of a qualitatively adequate preparatory process for these students. We implemented short-term workshops, in a control group, producing materials and incorporating methodologies that integrated theoretical and practical aspects of Geometric Design/Geometry. Our understanding is that these actions can be incorporated into the work dynamics of fellow teachers in their classrooms. We built, applied and analyzed tests associated with mapping the effectiveness of this pedagogical intervention process. Concluding positively by the intervention and the certainty that a planned action, with a longer duration, will raise to satisfactory levels the geometric thinking of the students involved.